Social Media Twitter @BGRM Indonesia as a Medium of Information Communication and Outreach - Herlan, Herlan; Hermansyah, Hermansyah; Pratama, Irfandi; Purnomo, Eko Priyo; Fathani, Aqil Teguh (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2023)
This study aims to analyze how social media, Twitter @BRGM Indonesia, is used as a communication medium for disseminating information and outreach and environmental campaigns related to peatland restoration and mangrove rehabilitation. This study uses a qualitative research approach with data analysis using the Nvivo 12 Plus software. This type of research data uses secondary data obtained and collected from @BRGM Indonesia’s twitter activity from March 2019 to October 2021, while supporting data is obtained from literature and social media. The research findings show that social media Twitter @BRGM Indonesia in its tweets is dominated by information related to peat restoration rather than mangrove rehabilitation. The findings reinforce that the previous BRGM was a BRG that focused on restoring peat after the great fires in 2015, and was considered to have completed its task in 2020, then added workload to rehabilitate mangroves. But the use of @BRGM Indonesia’s social media Twitter, still needs to be more effective, and the interaction only focuses on government agencies. At the same time, the information contained in the tweets mentioned does not match the contents.Keywords: Social media, environmental campaigns, peat restoration, mangrove rehabilitation, BRGM ABSTRAKPenelitian ini bertujuan untuk menganalisis bagaimana media sosial Twitter @BRGM Indonesia digunakan sebagai media komunikasi untuk menyebarluaskan informasi dan sosialisasi serta kampanye lingkungan terkait restorasi gambut dan rehabilitasi mangrove. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan analisis data menggunakan software Nvivo 12 Plus. Jenis data penelitian ini menggunakan data sekunder yang diperoleh dan dikumpulkan dari aktivitas twitter @BRGM Indonesia pada bulan Maret 2019 hingga Oktober 2021, sedangkan data pendukung diperoleh dari literatur dan media sosial. Hasil penelitian menunjukkan bahwa media sosial Twitter @BRGM Indonesia dalam cuitannya didominasi oleh informasi terkait restorasi gambut daripada rehabilitasi mangrove. Temuan itu memperkuat bahwa BRGM sebelumnya adalah BRG yang fokus memulihkan gambut pasca kebakaran hebat pada 2015, dan dianggap selesai tugasnya pada 2020, lalu menambah beban kerja untuk merehabilitasi mangrove. Namun penggunaan media sosial Twitter @BRGM Indonesia, masih perlu lebih efektif, dan interaksinya hanya terfokus pada instansi pemerintah. Sementara itu, informasi yang terkandung dalam tweet yang dibubuhi mention tidak sesuai dengan isinya.Kata Kunci: Media sosial, kampanye lingkungan, restorasi gambut, rehabilitasi mangrove, BRGM